A comprehensive study of the affective and physiological responses induced by dynamic virtual reality environments. (27th May 2019) - Cebeci, Berk; Celikcan, Ufuk; Capin, Tolga K.
Abstract: Previous studies showed that virtual reality (VR) environments can affect emotional state and cause significant changes in physiological responses. Aside from these effects, inadvertently induced cybersickness is a notorious problem faced in VR. In this study, to further investigate the effects of virtual environments (VEs) with different context, three dynamic VEs were created. Each VE had a particular purpose: evoking no emotion in Campfire (CF), unpleasant emotions in Hospital (HH), and cybersickness symptoms in Roller Coaster (RC). We made use of objective measurements of physiological responses such as pupil dilation, blinks, fixations, saccades, and heart rate, as well as subjective self‐assessments via pre‐ and post‐VE session questionnaires. While previous studies investigate different subsets of these measures, our study makes a comprehensive analysis of them jointly in dynamic VEs. The results of the study indicate that cybersickness produced higher saccade mean speed, whereas unpleasant context caused higher fixation count, saccade rate, and pupil dilation. Moreover, CF decreased anxiety, whereas HH and RC increased it and they also decreased comfort. Participants felt cybersickness in all VEs even in CF which is designed to minimize the effects. Abstract : In this study, to investigate the emotional and physiological effects of virtual environments (VEs) with different contexts, three dynamic VEs were created. Each VE had a particular purpose: evoking no emotion in Campfire (CF), unpleasant emotions in Hospital (HH), and cybersickness symptoms in Roller Coaster (RC). Results showed that cybersickness produced higher saccade mean speed, while unpleasant context caused higher fixation count, saccade rate, and pupil dilation; CF decreased anxiety, whereas HH and RC increased it and decreased comfort.